2013
DOI: 10.1021/jp407657d
|View full text |Cite
|
Sign up to set email alerts
|

The Weak Helps the Strong: Sigma-Holes and the Stability of MF4·Base Complexes

Abstract: Bonding interactions between an electron-deficient region (a sigma-hole) on M and electron donors in MF4-Base complexes, where M = C, Si, Ge, Sn, and Pb, are examined and rationalized. These interactions are seen to transition from weak primarily noncovalent interactions for all bases when M = C to stronger primarily covalent bonds in adducts as the valence shell expands for the heavier M atoms. For M = Ge, Sn, and Pb, the complexes are particularly stable. The consistent axial preference in these systems is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 37 publications
6
68
0
Order By: Relevance
“…[25,26,38,98,99] Previous studies have confirmed the trend that the tetrel bond grows stronger as T becomes larger, [30,32,33,47,100] but that the effect levels off between Sn and Pb. [45,101] An earlier work [45,102] supports the result noted here that the deformation energy induced within the Lewis acid molecule by formation of a tetrel bonded complex drops as the central tetrel atom grows in size. The ability of the heavier tetrel atoms to participate in two simultaneous noncovalent bonds is confirmed by earlier calculations [103] performed by Grabowski at the MP2 level, who also noted the possibility of both trans and cis structures, at least for Sn, for which the latter is more stable than the former by 3 kcal/mol, in nice agreement with our own findings.…”
Section: Discussionsupporting
confidence: 73%
“…[25,26,38,98,99] Previous studies have confirmed the trend that the tetrel bond grows stronger as T becomes larger, [30,32,33,47,100] but that the effect levels off between Sn and Pb. [45,101] An earlier work [45,102] supports the result noted here that the deformation energy induced within the Lewis acid molecule by formation of a tetrel bonded complex drops as the central tetrel atom grows in size. The ability of the heavier tetrel atoms to participate in two simultaneous noncovalent bonds is confirmed by earlier calculations [103] performed by Grabowski at the MP2 level, who also noted the possibility of both trans and cis structures, at least for Sn, for which the latter is more stable than the former by 3 kcal/mol, in nice agreement with our own findings.…”
Section: Discussionsupporting
confidence: 73%
“…Based solely on the arguments of the results of the MESP model, one might suggest [109,161,201,267] that the potentials of F in CF 4 are indicative of fluorine interacting only with electrophiles. From a later study reported elsewhere [158,268], it was found that that there are four positive σ-holes on the C atom directed along the outer extensions of the four F-C bonds, one would conclude that F• • • C(-F) in the crystal are genuine attractive contracts even though the r(F• • • C) are significantly longer-3.342 Å-than the sum of vdW radii of the C and F atoms (1.77 and 1.46 Å, respectively). While doing so, the importance of F• • • F interactions between the fluorine atoms of the interacting CF 4 molecules has probably to be neglected, as was done in the experimental studies [263][264][265][266].…”
Section: From the F• • • C And F• • • F Intermolecular Distances And mentioning
confidence: 98%
“…And indeed it is to these heavier atoms that most previous work has been devoted [18][19][20][21][22][23][24][25][26] . In the case of the C atom, its ability to engage in a TB has typically been amplified by adding a number of electron-withdrawing substituents like F [27][28][29] rather than considering a CH3 group itself. Our own lab has contributed to the current understanding of tetrel bonding as well [30][31][32][33][34][35] including the issue of steric crowding 26,36 and the manner in which such interactions might be used to design an effective selective anion receptor [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%